Development of a scalable single process for producing SARS-CoV-2 RBD monomer and dimer vaccine antigens - Boggiano-Ayo, Tammy; Palacios-Oliva, Julio; Lozada-Chang, Sumlai; Relova-Hernandez, Ernesto; Gomez-Perez, Jose; Oliva, Gonzalo; Hernandez, Lourdes; Bueno-Soler, Alexi; Montes de Oca, Daidee; Mora, Osvaldo; Machado-Santisteban, Roberto; Perez-Martinez, Dayana; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
We have developed a single process for producing two key COVID-19 vaccine antigens: SARS-CoV-2 receptor binding domain (RBD) monomer and dimer. These antigens are featured in various COVID-19 vaccine formats, including SOBERANA 01 and the licensed SOBERANA 02, and SOBERANA Plus. Our approach involves expressing RBD (319-541)-His6 in Chinese hamster ovary (CHO)-K1 cells, generating and characterizing oligoclones, and selecting the best RBD-producing clones. Critical parameters such as copper supplementation in the culture medium and cell viability influenced the yield of RBD dimer. The purification of RBD involved standard immobilized metal ion affinity chromatography (IMAC), ion exchange chromatography, and size exclusion chromatography. Our findings suggest that copper can improve IMAC performance. Efficient RBD production was achieved using small-scale bioreactor cell culture (2 L). The two RBD forms - monomeric and dimeric RBD - were also produced on a large scale (500 L). This study represents the first large-scale application of perfusion culture for the production of RBD antigens. We conducted a thorough analysis of the purified RBD antigens, which encompassed primary structure, protein integrity, N-glycosylation, size, purity, secondary and tertiary structures, isoform composition, hydrophobicity, and long-term stability. Additionally, we investigated RBD-ACE2 interactions, in vitro ACE2 recognition of RBD, and the immunogenicity of RBD antigens in mice. We have determined that both the monomeric and dimeric RBD antigens possess the necessary quality attributes for vaccine production. By enabling the customizable production of both RBD forms, this unified manufacturing process provides the required flexibility to adapt rapidly to the ever-changing demands of emerging SARS-CoV-2 variants and different COVID-19 vaccine platforms.